2018
DOI: 10.5385/nm.2018.25.2.58
|View full text |Cite
|
Sign up to set email alerts
|

Breast Milk-Transmitted Cytomegalovirus Infection in Preterm Infants

Abstract: Purpose: The purpose of this study is to describe the rate of cytomegalovirus (CMV) virolactia, and the prevalence of breast milk (BM)-transmitted postnatal CMV infection among premature infants after freeze-thawing (FT) and Holder pasteurization (HP) of breast milk. Methods: This is a single-center, retrospective study of 312 infants born at less than 32 weeks of gestation, or with a birth weight less than 1,500 g from January 2013 to June 2017. All infants were screened for CMV-specific immunoglobulin (Ig) G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Some studies have reported poor neurocognitive outcomes in adolescents born preterm with pCMV infection. In contrast, other studies have shown that preterm infants might not have an increased risk for neurological sequelae, and the differences in neurocognitive outcome could only be detected in higher ages, >6 years ( 2 , 8 , 12 , 16 , 18 , 30 , 31 ). Further research is required to understand the disease burden and establish guidelines for the prevention and management of pCMV infection in preterm infants from CMV-seropositive mothers.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Some studies have reported poor neurocognitive outcomes in adolescents born preterm with pCMV infection. In contrast, other studies have shown that preterm infants might not have an increased risk for neurological sequelae, and the differences in neurocognitive outcome could only be detected in higher ages, >6 years ( 2 , 8 , 12 , 16 , 18 , 30 , 31 ). Further research is required to understand the disease burden and establish guidelines for the prevention and management of pCMV infection in preterm infants from CMV-seropositive mothers.…”
Section: Discussionmentioning
confidence: 77%
“…The maternal CMV-IgG positivity rate was reported to be in the range 52%–97% ( 8 ). In Korea, ≥80% of women have CMV antibodies by childbearing age, and the CMV transmission rate from mothers to preterm infants through breast milk is estimated to be high ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%